LncRNA DUXAP8 induces breast cancer radioresistance by modulating the PI3K/AKT/mTOR pathway and the EZH2-E-cadherin/RHOB pathway. Issue 1 (31st December 2022) - Lei, Changjiang; Li, Shaoting; Fan, Ying; Hua, Li; Pan, Qingyun; Li, Yuan; Long, Zhixiong; Yang, Rui
ABSTRACT: Radiation resistance poses a major clinical challenge in breast cancer (BC) treatment, but little is known about how long noncoding RNA (lncRNA) may regulate this phenomenon. Here, we reported that DUXAP8 was highly expressed in radioresistant BC tissues, and high expression of DUXAP8 was associated with poor prognosis. We found that the overexpression of DUXAP8 promoted radioresistance, while the knockdown of DUXAP8 expression increased radiosensitivity. Further studies revealed that DUXAP8 enhanced the radioresistance of BC cells by activating the PI3K/AKT/mTOR pathway and by repressing the expression of E-cadherin and RHOB through interaction with EZH2. Together, our work demonstrates that the overexpression of DUXAP8 promotes the resistance of BC cells toward radiation through modulating PI3K/AKT/mTOR pathway and EZH2-E-cadherin/RHOB axis. Targeting DUXAP8 may serve as a potential strategy to overcome radioresistance in BC treatment.